BAND GAP MODULATION OF GRAPHENE AND GRAPHYNE VIA TETRACYANOETHYLENE ADSORPTION - MAJIDI, Roya; KARAMI, Alireza (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Adsorption of tetracyanoethylene molecule on graphene and graphyne was investigated in view of finding an effective way to control their electronic properties. The electronic properties of graphene, α-, β- and γ- graphyne were studied by using the density functional theory. The binding energy, equilibrium adsorption distance, amount of charge transfer, electronic band structure, and density of states were calculated. The small adsorption energy and large adsorption distance identified physisorption of tetracyanoethylene molecule on graphene and graphyne sheets. It was found that charge is transferred from sheets to tetracyanoethylene molecule. In the presence of this acceptor molecule, the graphene and α-, β- and γ-graphynes, with semimetallic properties, show semiconducting behaviour. The tetracyanoethylene molecule has no considerable effect on the semiconducting property of γ-graphyne. Our results reveal that adsorption of organic molecules, such as tetracyanoethylene, is a proper method to open a band gap in graphene and graphyne.